Pengaruh Campuran Kascing dengan Media Semai Tembakau (Nicotinia tabacum L.) Terhadap Penyakit Rebah Semai (Rhizoctonia solani KUHN.) di Rumah Kaca - Hartati Oktarina (Fakultas Pertanian, Universitas Syiah Kuala, 2007)
The effect of Vermicompost and Tobacco Seedling Mixture on Damping-off (Rhizoctonia solani KUHN.) in Green HouseABSTRACT. This research objective was to determine the dosage of vermicompost that could suppres the disease intensity on tobacco (N. tabaccum). The experiment was carried out in the green house of the Department of Plant amd Disease, Faculty of Agriculture, Padjajaran University from July to August 2005. The experiment was arranged in the randomized completely block design using six treatment and four replications. The treatments were the mixture of seedling media and vermicompost at 1:1, 1:2, and 1:3, seedling media with propineb 70%, mixture of soil and bamboo leaf charcoal without vermicompost, and soil layered by bamboo leaf charcoal without vermicompost as control. The result showed that vermicompost mixed into tobacco seedling media could suppres the disease intensity. The dosage of the vermicompost at the ratio of 1:1, 1:2, and 1:3 suppressed 80,00%; 90,00%, and 92,50% of damping off disease intensity on tobacco respectively.